Upaya Peningkatan Kualitas Pembelajaran Fisika Melalui Pelatihan Digital Image Creator for Optical Microscope (DIGICOM) pada Guru Fisika Batang (UPEJ Unnes Physics Education Journal, 2020)
Teaching physics by utilizing technology becomes a necessity for high school physics teachers to master. DIGICOM is an innovation in teaching physics that utilizes multi-technology. Interface-connected camera technology can help explain microscopic phenomena observed through a microscope. A total of 19 physics teachers in Batang Regency, Central Java received training on DIGICOM-based science learning. From the preliminary data it is known that almost all teachers have never carried out learning using multi-technology and only 50% of teachers or schools have digital microscopes and digital cameras in their schools. But after getting DIGICOM training in physics learning, teachers already have sufficient knowledge and they have the confidence to be able to implement the results of this training in learning physics in their classrooms.